2022
DOI: 10.3389/fenrg.2021.813978
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Fracturing Fracture Deformation Mechanism of Shale Reservoir

Abstract: After large-scale sand fracturing of horizontal wells in shale gas reservoir, fracturing fractures will deform in the production process. However, fracture deformation will lead to the decrease in fracture conductivity and then cause the decrease of gas well productivity. Therefore, in order to evaluate the fracturing fracture deformation mechanism of shale reservoirs, the shale proppant-supported fracture deformation evaluation experiments were carried out under different proppant types, particle sizes, sandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In addition, silicon dioxide acid displays distinct behavior in limestone as compared to shale. The researchers noted that the fracture conductivity of shale rock demonstrated superior enhancements when compared to limestone rock [ 145 ]. The study also revealed that there exists an optimal concentration for improving the rheological properties of surfactant-based fluids for hydraulic fracturing applications, and higher concentrations are not recommended [ 144 , 145 ].…”
Section: Nanoparticle Utilization In the Oil And Gas Industrymentioning
confidence: 99%
“…In addition, silicon dioxide acid displays distinct behavior in limestone as compared to shale. The researchers noted that the fracture conductivity of shale rock demonstrated superior enhancements when compared to limestone rock [ 145 ]. The study also revealed that there exists an optimal concentration for improving the rheological properties of surfactant-based fluids for hydraulic fracturing applications, and higher concentrations are not recommended [ 144 , 145 ].…”
Section: Nanoparticle Utilization In the Oil And Gas Industrymentioning
confidence: 99%